2018
DOI: 10.1016/s0140-6736(17)32404-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic or surgical step-up approach for infected necrotising pancreatitis: a multicentre randomised trial

Abstract: The Dutch Digestive Disease Foundation, Fonds NutsOhra, and the Netherlands Organization for Health Research and Development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
544
8
16

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 575 publications
(624 citation statements)
references
References 32 publications
24
544
8
16
Order By: Relevance
“…The mortality rate of 9.4% is comparable to that of contemporary studies, which range from 7% to 25% . All patient deaths in our series were unrelated to their procedures.…”
Section: Discussionsupporting
confidence: 78%
“…The mortality rate of 9.4% is comparable to that of contemporary studies, which range from 7% to 25% . All patient deaths in our series were unrelated to their procedures.…”
Section: Discussionsupporting
confidence: 78%
“…5,6 If expertise is available, endoscopic drainage of symptomatic PFCs that abut the stomach or duodenum is preferred to percutaneous or surgical approaches. 79 Percutaneous drainage carries the risk of pancreaticocutaneous fistula formation in up to 14% of patients. 1012 Surgical approaches have high morbidity (25%) and mortality (5%).…”
mentioning
confidence: 99%
“…In the step-up approach, nearly half of the patients can be treated with drainages alone, the other half require additional different procedures for the final treatment, including percutaneous, endoscopic, open, or minimally invasive surgery [17, 50, 52, 53]. In a systematic review including 10 retrospective series and one RCT with 384 patients who underwent percutaneous drainage because of acute necrotizing pancreatitis, percutaneous drainage was sufficient as definitive treatment in 56% of patients [54].…”
Section: Management Of Acute Necrotic Collections and Walled-off Necrmentioning
confidence: 99%
“…Compared to surgical necrosectomy, an endoscopic approach significantly reduces proinflammatory response and improves clinical outcome in ANP patients [52]. However, when used as a single modality approach, it requires more sessions of necrosectomy for definitive treatment than in combination with other interventional procedures [53, 61-63]. A large meta-analysis found that endoscopic necrosectomy has success rate of 81% as a single treatment modality with a complication rate of 36% [64].…”
Section: Management Of Acute Necrotic Collections and Walled-off Necrmentioning
confidence: 99%
See 1 more Smart Citation